Production of water tolerant melamine-urea-formaldehyde resin by incorporation of sodium metabisulphite - Nádia T. Paiva (2016)
The aim of this work was the development of a new MUF resin formulation with high tolerance towards water dilution, and a good overall performance in terms of physico-mechanical properties and formaldehyde emissions. For this purpose, sodium metabisulphite (MTBS) was added during melamine condensation reaction, therefore decreasing its extent by blocking amino groups. It was found that the resins with higher amounts of MTBS have obtained the higher water dilution capacity (a percentage of 6% of MTBS resulted in a resin with a water tolerance about 60 times higher than the one present in a resin without MTBS incorporation). The molecular weight distribution showed that the resins produced with MTBS have a different polymeric structure. Regarding particleboard production and evaluation, it was possible to conclude that the increase in MTBS addition lowers the internal bond strength and formaldehyde emissions. However, with the resin, having the MTBS addition of 6%, it was still possible to obtain the panel with internal bond strength higher than the acceptable minimum (0.45 N mm(-2)), with a pressing time of 150 s. When compared with commercial MUF resins, the formulation developed in this work presents lower values of formaldehyde emissions, complying to CARB II regulation, even though with somewhat inferior physico-mechanical performances.